"A to P" Screw Versus Posterolateral Plate for Posterior Malleolus Fixation in Trimalleolar Ankle Fractures. Issue 4 (April 2015) - O'Connor, Timothy J.; Mueller, Benjamin; Ly, Thuan V.; Jacobson, Aaron R.; Nelson, Eric R.; Cole, Peter A.
Abstract : Objectives: To compare radiographic and clinical midterm outcomes of posterior malleolar fractures treated with posterior buttress plating versus anterior to posterior lag screw fixation. Design: Retrospective case series. Setting: Level I trauma center. Patients/Participants: Between January 2002 and December 2010, patients with posterior malleolar fractures were identified by Current Procedural Terminology code and their charts reviewed for eligibility. Intervention: Posterior malleolar fixation using either anterior to posterior (AP) lag screws or posterior buttress plating. Main Outcome Measurements: Demographic data, length of follow-up, range of motion, and postoperative Short Musculoskeletal Function Assessment (SMFA) scores were the main outcome measurements. Immediate postoperative radiographs for residual gap/step-off and final follow-up radiographs for the degree of arthritis that developed were evaluated. Results: Thirty-seven patients were eligible for the study, and 27 chose to participate. Sixteen patients underwent posterior buttress plating, and 11 underwent AP screw fixation with mean follow-up times of 54.9 and 32 months, respectively. Demographic data were similar between groups. The posterolateral plating group demonstrated superior postoperative SMFA scores compared with the AP screw group with statistically significant differences in the SMFA bother index (26.7 vs. 9.2, P = 0.03) and trends toward improvement in the mobility (28.3 vs. 12.9, P = 0.08) and functional indices (20.2 vs. 9.4, P = 0.08). There were no significant differences in the range of motion or the development of ankle arthritis over time. Conclusions: Patients with trimalleolar ankle fractures in whom the posterior malleolus was treated with posterolateral buttress plating had superior clinical outcomes at follow-up compared with those treated with AP screws. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.